New generations at work attracting, recruiting, retraining & training Generation Y - McCrindle, Mark.; McCrindle Research Pty Ltd (Baulkham Hills, N.S.W. : McCrindle Research, 2006)
"Over the last couple of years the realities of massive generational change have dawned on many business leaders. While the issues of an ageing population and a new attitude to work have literally been emerging for a generation, it has been a sudden awakening for many organisations. In fact dealing with these demographic changes and pecifically recruiting, retaining and managing Generation Y has emerged as one of the biggest issues facing employers today ... This whitepaper came as the result of the need for significant original research into Generation Y; both qualitative and quantitative."--Foreword.
"... in 2006 Mark McCrindle of McCrindle Research was commissioned to conduct some groundbreaking research into Generation Y and their attitudes to work."--Foreword.
At head of title: McCrindle Research.
Title from title screen (viewed on 7th August 2006).
Includes bibliographical references.
Text and graphics.
Mode of access: Internet via World Wide Web. On 7/08/2006 available from website of McCrindle Research at: http://www.mccrindle.com.au
Keywords: Generation Y -- Employment -- Australia; Generations -- Australia